Intranasal Lipid Particulate Drug Delivery Systems: An Update on Clinical Challenges and Biodistribution Studies of Cerebroactive Drugs in Alzheimer’s disease - Arora, Deepshi; Bhatt, Shailendra; Kumar, Manish; Vattikonda, Hari D.C.; Taneja, Yugam; Jain, Vishal; Joshi, Veenu; Gali, Chaitanya C. (Current Pharmaceutical Design, 2020)
Background: Alzheimer's is the primary cause of death in the various countries that affect wide strata of the population. The treatment of it is restricted to a few conventional oral medications that act only superficially. It is evident that the delivery of a drug to the brain across the blood-brain barrier is challenging as the BBB is armed with several efflux transporters like the P-glycoprotein as well as nasal mucociliary clearance adds up leading to decreased concentration and reduced therapeutic efficacy. Considering these, the intranasal IN route of drug administration is emerging as an alternative route for the systemic delivery of a drug to the brain. The intranasal (IN) administration of lipid nanoparticles loaded with cerebroactive drugs showed promise in treating various neurodegenerative diseases, since the nasal route allows the direct nose to brain delivery by means of solid lipid nanoparticles (SLN’s). The tailoring of intranasal lipid particulate drug delivery systems is a pleasing approach to facilitate uptake of therapeutic agents at the desired site of action, particularly when a free drug has poor pharmacokinetics/ biodistribution (PK/BD) or significant off-site toxicities. Objectives: 1) In this review, key challenges and physiological mechanisms regulating intranasal brain delivery in Alzheimer’s disease, ex vivo studies, pharmacokinetics parameters including brain uptake and histopathological studies are thoroughly discussed. 2) A thorough understanding of the in vivo behaviour of the intranasal drug carriers will be the elusive goal. 3) The article emphasizes to drag the attention of the research community working in the intranasal field towards the challenges and hurdles of the practical applicability of intranasal delivery of cerebroactive drugs. Method: Various electronic databases, journals like nanotechnology and nanoscience, dove press are reviewed for the collection and compilation of data. Results: From in vivo biodistribution studies, pharmacokinetics parameters, and gamma scintigraphy images of various drugs, it is speculated that intranasal lipid particulates drug delivery system shows better brain targeting efficiency for various CNS disorders in comparison to other routes. Conclusion: Various routes are explored for the delivery of drugs to increase bioavailability in the brain for CNS disorders but the intranasal route shows better results that pave the way for success in the future if properly explored.
Keywords: lipid carriers